(untitled) (دراسات أقليمية, 2009)
Historic experiences have resulted in various meanings for citizenship in ideology and in practice. According to historians, these meanings varied being near or far from the contemporary concept of citizenship. Even in the contemporary history the results of citizenship concept were varied according to ideological, political, and social streams which cannot be read, understood, or criticized away from the surrounding circumstances or away from time and place with all their political, economic, social, ideological, and educational dimensions. Then sound authentication for the concept of citizenship as a result for one simple thought cannot be done. Citizenship has raised and grew under numerous thought schools varied in their theories, beliefs, and even in the circumstances of their establishment on the local, national, and international levels. Since the issue of citizenship is regarded as an essential axis in the modern democratic theory and practice, then determining its dimensions and the way it should be practiced sprout from the way this regime or that gives citizenship rights for all, besides the level of citizen's awareness and their adherence to do